Study of Ropivacaine Block to Reduce Post- Operative Pain after Strip Harvesting, And Relation of Width of Strip to Post-Operative Pain - Dr. Seema Garg, Dr. Anil Kumar Garg (International Journal of Innovative Research in Medical Science, 2017)
Introduction - Strip method of follicle harvesting has great advantage but Post-operative pain as well as fear of pain is commonest complain of this surgery. Severity of post-operative pain is in direct relation to width of strip harvested. It is mandatory to reduce post-operative pain to make this method more acceptable for patients. Objective - This study was done to know the effect of Ropivacaine infiltration post operatively and width of harvested strip on donor site pain. Method- Grading was given by author for post-operative pain. Grading done on criteria of severity of pain and post-operative sleep disturbance. Initial data were collected from patients about pain severity and sleep disturbance from cases where strip was 2 cm wide and it was noted that pain incidence was very high. Then in test group post operatively Ropivacaine 0.5 % was infiltrated along suture line. In second study - the strip was 1.5 cm in centre and 1 cm on lateral side. Again in test group Ropivacaine infiltration given post operatively while in control group no infiltration given. Data were collected and analysed. Observation - There was significant pain in patient where strip width was 2 cm as compare to patients where strip width was 1.5 cm. There was significant reduction of pain in those with strip width 1.5 cm and infiltration of Ropivacaine was done. Conclusion - Severity of pain is directly proportional to width of harvested strip. The post-operative infiltration of Ropivacaine 0.5 % along suture line significantly reduces post- operative pain